Impulse control behaviours in a Malaysian Parkinson’s disease population - Md. Rani, Shahrul Azmin; Tan, Eng Liang; Nik Jaafar, Nik Ruzyanei; Zakaria, Hazli; Mohammed Nawi, Azmawati; Law, Zhe Kang; Remli, Rabani; Wan Yahya, Nafisah; Ramesh, Sahathevan; Tan, Hui Jan; Mohamad Pakarul Razy, Nur Fadhlina; Abdul Murad, Nor Azian; et al. (ASEAN Neurological Association, 2016)
Background: Impulse control behaviours are repetitive and excessive activities that may be sub-syndromal and not fulfill the criteria for impulse control disorder. These activities have potential to negatively impact on the daily lives of sufferers. We conducted a study to investigate the prevalence of impulse control behaviors and its associated features in Parkinson’s disease in our population. Methods: We conducted a prospective cross-sectional study on consecutive patients attending neurology clinic. Inclusion criteria include idiopathic Parkinson’s disease patients with Hoehn & Yahr stage I-IV. Eighty patients were enrolled and screened for impulse control behaviors using the Questionnaire for Impulsive-Compulsive Disorder for Parkinson’s disease (QUIP). Results: Prevalence of impulse control behaviors among our cohort was 11.3%; the features significantly associated with it were higher level of education (p=0.02), advanced stage of disease (p=0.03) and higher levodopa dosage (p= 0.01). The commonest impulse control behavior in our cohort was compulsive medication use (7.5%), followed by hobbyism (6.3%), hypersexuality (5%), compulsive buying (3.75%), punding (2.5%), walkabout (2.5%), compulsive eating (1.25%) and pathological gambling (1.3%). Conclusions: There is an association between impulse control behavior and higher levodopa dosage in a study on patients with Parkinson’s disease in Malaysia. We also found a low prevalence of pathological gambling as compared to studies performed in the West.